Meningkatkan Minat dan Hasil Belajar Seni Tari Melalui Pendekatan PAIKEM Berbantuan Metode Demonstrasi Semester 2 Siswa Kelas VII-3 SMP Negeri 5 Penajam Kabupaten Penajam Paser Utara Provinsi Kalimantan Timur Tahun Pelajaran 2019/2020 - Sahria Sahria (Journal on Education, 2022)
Cultural Arts at SMP Negeri 5 Penajam, PPU Regency applies Integrated Cultural Arts lessons which have been developed based on the 2013 Curriculum by considering, Complexity, carrying capacity, student context. In addition to the above, the diversity of students' talents and interests is also one of the reasons for the implementation of integrated Cultural Arts lessons. However, with the amount of material and the limited time for face-to-face hours, several obstacles arise related to students. Students find it difficult, especially in dance subjects that are rarely studied at the previous school level, causing a lack of interest and student participation in the learning process. These obstacles need to be considered and find a way out by the teacher as a motivator, facilitator and evaluator in the learning process. The purpose of this research is to find out: 1) the teacher's efforts in the learning process to increase the interest of Class VII-3 students of SMP Negeri 5 Penajam in learning dance. 2) the teacher's efforts in improving student learning outcomes for Class VII-3 SMP Negeri 5 Penajam in dance lessons. This research will apply the Active, Creative, Effective, and Fun Learning (PAKEM) approach which is divided into two cycles. Based on the results of classroom action research, the teacher's efforts by applying the PAIKEM approach combined with the Demonstration technique can increase students' interest and learning achievement in the arts and culture subjects of the dance branch with competency standards for expressing themselves through dance works, especially in the basic competence of exploring floor movement patterns. dance in pairs/local groups. In the first cycle of 32 students who completed it reached 59.37% or 19 students and who did not complete there were 40.62% or 13 students, and the average score was 74.53. While in the second cycle of the 32 students who successfully completed there were 30 students or 92.75%, and the average value was 79.84. Based on the conclusions above, the research was stopped until the second cycle.